Implementation of Islamic Marketing Ethics on Digital Marketing to Increasing The Competitive Advantage of MSMEs - Zaroni, Akhmad Nur; Norvadewi, Norvadewi (ITB AAS Indonesia Surakarta, 2024)
The development of the current digital era forces businesses to adapt and change so that entrepreneurs turn to online and digital businesses, especially in marketing, providing and shipping products sold. Muslim entrepreneurs must pay attention to ethics in their business activities so that marketing and business promotion activities carried out digitally must align with the values and principles of business ethics in Islam. This qualitative study seeks to illustrate how MSME digital marketing and business ethics values are applied and how their impact increases the competitive advantage of MSMEs in East Kalimantan. The research was conducted on 24 MSMEs in various business fields. The data collection technique uses interviews conducted with MSME actors and several consumers; besides that, data is also supported by observation and documentation. The data were analyzed using Miles and Huberman's model qualitatively. The study's results found: 1) various forms of digital marketing used by MSMEs are Facebook, WhatsApp, Instagram, Gojek, Grab, and Shopee, 2) The application of Islamic Marketing Ethics to MSME entrepreneurs has been carried out by being friendly to buyers offline and online, being honest (Siddiq) with the products marketed, and there is no fraud mandate in product delivery (Amanah), 3) Applying Islamic marketing ethics to digital marketing makes the business development with an increase in sales, relation and can increase the business's competitiveness.